Conceptual Framework for Feasibility Evaluation of Rest and Service Area (TIP) Development Project on JORR II Toll Road Based on Value Engineering - Subki, Muhammad; Karim, Rully Andhika (Journal La Multiapp, 2025)
Infrastructure development, particularly toll roads, requires substantial investment and involves a long payback period. According to data from BPJT, Indonesia currently operates more than 2,816 km of toll roads, an increase of 197% or 1,867.7 km compared to 2014. However, this growth has not been matched by the development of Rest and Service Areas (TIP), which are essential facilities for toll road users. Government Regulation No. 17 of 2021 mandates the provision of at least one TIP for every 50 km of toll road. In the case of the 110.74 km JORR II Toll Road, a TIP was planned as part of the Cengkareng–Batuceper–Kunciran section. However, the BUJT has been unable to construct the TIP due to delays in land acquisition and the absence of a defined investment cost by the government. This delay contributes to a prolonged deficit cash flow period for the toll road section. This study aims to provide a conceptual framework to improve the financial feasibility of TIP projects by examining the financial viability of toll road and TIP developments and identifying potential improvement strategies. Literature reviews indicate that a value engineering approach can enhance financial feasibility by optimizing construction costs and creating new revenue streams. Therefore, this study will adopt the value engineering concept as the main strategy to improve the financial feasibility of the TIP project.